Paleoenvironmental shifts and precipitation variations recorded in tropical maar lake sediments during the Holocene in Southern China. (October 2014) - Yang, Xiaoqiang; Wei, Gangjian; Yang, Jie; Jia, Guodong; Huang, Chenchen; Xie, Luhua; Huang, Wenya; Argyrios, Kapsiotis
Tropical ocean–atmosphere system exerts powerful control on the precipitation variations around the Pacific Ocean area where interactions among monsoon system, Intertropical Convergence Zone (ITCZ) migration, and other tropical ocean circulations modulate the regional climate changes in centennial-scale. However, little high-resolution information is known about the paleoenvironment changes in this area during the Holocene. In this study, a composite sediment profile, approximately 16 m in length, recovered from Shuangchiling (SCL) maar lake in Hainan Island, northern margin of western tropical Pacific, was selected to investigate the lake-level fluctuations, net precipitation variations, and the influence of the ocean–atmosphere system. Stable isotope (δ 13 C, δ 15 N) analyses, total organic carbon (TOC), and total nitrogen (TN) concentration measurements, as well as grain-size estimations revealed a two-stage evolution scenario for the lake dating back to 9 cal. kyr BP. The first stage spans a period of time from 9 to 3 cal. kyr BP, once the lake was characterized by shallow or ephemeral conditions. The second stage occurred from 3 to 0.6 cal. kyr BP and was characterized by a deeper water environment with substantial lake-level changes. All climate proxies suggest that the ocean–atmosphere variabilities, such as El Niño-Southern Oscillation (ENSO) and Pacific Decadal Oscillation (PDO) activities, had a dominant influence on the regional net precipitation (the difference between precipitation and evaporation) and lake-level fluctuations. A three-step change of clay percentage at 3, 2.2, and 1.3 cal. kyr BP correlate well with the ENSO proxy records from the eastern tropical Pacific.